Nonresident Undergraduates’ Performance in English Writing Classes— Hierarchical Linear Modeling Analysis - Vaughn, Allison A.; Bergman, Matthew; Fass-Holmes, Barry (Journal of International Students, 2015)
Do undergraduates whose native language is not English have writing deficiencies leading to academic struggles? The present study showed that the answer to this question was “no” at an American West Coast public university. This university’s nonresident undergraduates on average earned B- to B+ in their colleges’ English intensive-writing programs’ classes, C in community college English classes, and term grade point averages between 2.5 (C+ to B-) and 3.2 (B) in the fall term of the five most recent academic years. Hierarchical linear modeling analyses showed that the predictors with the largest effect sizes were English writing programs and class level; however, each predictor accounted for less than 25% of the total variance.